Human Cadaver Study Evaluating a New Measurement Technique for Graft Volumes after Sinus Floor Elevation. (10th July 2012) - Platzer, Susanne; Wildburger, Angelika; Lorenzoni, Martin; Jakse, Norbert; Riedl, Regina; Weiglein, Andreas; Wegscheider, Walther; Kirmeier, Robert
ABSTRACT Purpose: Volumetric data can be used as complementary information to characterize grafting materials. The aim of this cadaveric study was to analyze a noncommercial measurement technique based on the novel concept of an "interactive rigid registration algorithm" (IRRA). Parameters analyzed included the reproducibility of IRRA measurements and their reliability in comparison with the established measurement technique of "region growing segmentation thresholding" (RGST). Materials and Methods: Three human skulls were used to simulate a total of 18 sinus grafts, using three incremental grafting procedures in each sinus (three skulls × two sinuses × three grafting increments). Radiopaque impression material was used for the simulated grafts, whose volumes were recorded by computed tomography from three different tilt angles. The reproducibility of IRRA measurements and the reliability of volumetric results obtained with both the IRRA and RGST techniques were evaluated by appropriate intraclass correlation coefficient (ICC) and Bland–Altman analysis. Results: ICC greater than 0.9 indicated close to perfect agreement of the results obtained with both methods and good reproducibility of the IRRA measurements. Bland–Altman analysis demonstrated good inter‐method and intramethod agreement. Conclusions: The IRRA measurement technique can be recommended as a noninvasive tool to evaluate graft volumes in human maxillary sinuses.